A Chandra Survey of the SMC Bar - McDowell, J. C.; Zezas, A.; Kalogera, V.; Hatzidimitriou, D.; Fabbiano, G. (American Astronomical Society Meeting Abstracts #202, 2003)
We present preliminary results from our Cycle 3 Chandra survey of the central region of the Small Magellanic Cloud. Five ACIS-I fields cover a large fraction of the bar. The images show at least ten bright, extended, supernova remnants and two bright, previously unknown, transients; point sources are detected down to a luminosity of log L(erg/s) = 33. We have obtained exposure-corrected luminosity functions for each field.